2020
DOI: 10.4236/ojbm.2020.85122
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Corporate Governance Characteristics on Environmental Performance: The Case of Food and Beverage Sector

Abstract: The purpose of this study is to investigate the effect of the main Corporate Governance (CG) characteristics on the corporate environmental performance. In addition, it focuses on global food companies as this sector is distinguished by specific characteristics. The sample of the study employs 174 food companies from the Thomson Reuters Global Food & Beverages Price Return Index for 2017. The Environmental Score as calculated by Thomson Reuters is adopted in the proposed model as a proxy of corporate Environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Additionally, the study of Shahbaz, Karaman, Kilic, and Uyar [77] discovered that the non-executive directors are positive and significantly influenced environmental disclosure. As well, the study of Giannarakis, Sariannidis, and Konteos [32] on the influence of corporate governance on environmental practice in Greece concluded that the board size and existence of a female on board have favourable impact of environmental practices.…”
Section: Review Of Extant Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the study of Shahbaz, Karaman, Kilic, and Uyar [77] discovered that the non-executive directors are positive and significantly influenced environmental disclosure. As well, the study of Giannarakis, Sariannidis, and Konteos [32] on the influence of corporate governance on environmental practice in Greece concluded that the board size and existence of a female on board have favourable impact of environmental practices.…”
Section: Review Of Extant Literaturementioning
confidence: 99%
“…A checklist of environmental sustainability disclosure was developed, and it was proxied by eight disclosure indicators as shown in Appendix. A score of '1' was assigned to an item if it is available in the firm's annual account and a score of '0' if the information is absent [5,32]. Content analysis was conducted to ascertain the absence or presence of a specific disclosure in the annual reports based on the environmental sustainability disclosure checklist developed [44,62].…”
Section: Dependent Variablementioning
confidence: 99%
“…The figure of the directors, executive, non-executive, and independent non-executive represents the size of a board (Brammer & Pavelin, 2006;Giannarakis, Sariannidis, & Konteos, 2020). Stakeholder theory opines that the larger the board, the more benefits in facilitating the firm's fairness and development; and it determines the efficacy of company in meeting the stakeholders' requirements of voluntary disclosure of sustainability practices (Ntim, Soobaroyen, & Broad, 2017).…”
Section: Review Of Extant Literaturementioning
confidence: 99%
“…2019), Japan (Endo 2020), and the United Kingdom (Giannarakis et al. 2020). Very few studies focus on developing countries or emerging economies as research contexts relevant to EID (Adinehzadeh et al.…”
Section: Introductionmentioning
confidence: 99%